An optical sensor array discriminates syrups and honeys - Bojanowski, Maximilian; Hainer, Felix; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
Abstract We report a cross-reactive sensor array, combining a two-component probe system based upon three viologen substituted boronic acids and a poly(aryleneethynylene) (PAE) and an additional number of simple PAEs alone. This combined system discriminates 27 different honeys in aqueous solution, according to patterns in fluorescence intensity modulation, using linear discriminant analysis for data processing. The fluorescence turn-on array detects saccharide composition, while the PAEs discriminate trace colored components in the honeys.
Gesehen am 07.04.2020